Effect of cold stress on growth and yield of boro rice genotypes - Akter, S E; Mondal, M M A; Khanam, S (Bangladesh Journal of Nuclear Agriculture, 2025)
During the Boro season of 2023-24, the experiment was carried out at the experiment field of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, Bangladesh to assess the effect of cold stress on growth and yield of rice plant and to identify cold stress tolerant rice genotypes. The experiment was set in a two factorial RCBD with three replications. The first factor was three date of transplanting: D/T1: 30/11/23, D/T2: 12/12/23 and D/T3: 28/12/23 and the second factor was seven rice genotypes (BNCR-20, BNCR-35, BNCR-45, BNDR 18, BNDR-48, BNDR-57 and BRRI dhan67). Rice plant faced the most critical low temperature in January, 24 that is below 15o C. The best performance of physiological parameters like SPAD, TDM, CGR, RGR, NAR and LAI was observed in BNCR-45, BNDR-48, BNDR-48, BRRI dhan67, BRRI dhan67 and BNDR-57 genotype, respectively. On the other hand date of transplanting (D/T3: 28/12/23) performed better in terms of SPAD, TDM, CGR, RGR, NAR and LAI. The highest no. of filled grain panicle-1, straw dry weight (t ha-1), grain yield (t ha-1) was recorded in BNDR-18. Among the date of transplanting, 28 December transplanting showed better performance in terms of yield and yield contributing characters. The highest grain yield (t ha-1) was recorded in BNDR-18 when transplanted at 28 December and the lowest was recorded when transplanted at early i.e. November. Bangladesh J. Nuclear Agric, 38(2): 35-47, 2024